2009
DOI: 10.1038/ijo.2009.79
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of gut hormone and metabolic changes after adjustable gastric banding and Roux-en-Y gastric bypass

Abstract: ObjectiveThe objective of this study was to quantify hormones that regulate energy and glucose homeostasis in order to establish possible mechanisms for the greater efficacy of Roux-en-Y gastric bypass (RYGB) compared with laparascopic adjustable gastric banding (LAGB) in achieving weight loss and improved insulin sensitivity.DesignLongitudinal study of patients undergoing LAGB (n=15) and RYGB (n=28) who were studied prior to surgery and at 2, 12, 26 and 52 wks afterwards.MeasurementsFasting blood samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
277
2
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(300 citation statements)
references
References 45 publications
13
277
2
8
Order By: Relevance
“…25,26 The difference in insulin resistance in the postoperative period between the 2 procedures found in this meta-analysis also supports the theory that duodenum exclusion is helpful for the reduction of insulin resistance. In recent studies, Korner and colleagues 27 found that reduction of insulin resistance correlated significantly with weight loss only in patients who underwnt gastric banding, not in those who had gastric bypass, and Bikman and colleagues 28 found that improved insulin sensitivity after gastric bypass was due to something other than weight loss. Because the duodenum was recently found to have a novel intestine-brain-liver neurocircuit to increase hepatic insulin sensitivity, it is possible that gastrointestinal surgery may help mediate antidiabetes effects, although this is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 The difference in insulin resistance in the postoperative period between the 2 procedures found in this meta-analysis also supports the theory that duodenum exclusion is helpful for the reduction of insulin resistance. In recent studies, Korner and colleagues 27 found that reduction of insulin resistance correlated significantly with weight loss only in patients who underwnt gastric banding, not in those who had gastric bypass, and Bikman and colleagues 28 found that improved insulin sensitivity after gastric bypass was due to something other than weight loss. Because the duodenum was recently found to have a novel intestine-brain-liver neurocircuit to increase hepatic insulin sensitivity, it is possible that gastrointestinal surgery may help mediate antidiabetes effects, although this is currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, dieting-induced weight loss is accompanied by an active "defense" of the higher body weight (34). Notably, in the case of RYGBP, the sustained body weight reduction occurs despite dramatic falls in circulating leptin levels (35). However, RYGBP-induced gut hormonal changes contrast strongly with those seen after dieting, as the former result in reduced hunger and more satiety, which lead to sustained weight loss (36).…”
Section: Mechanisms Underlying Effects Of Rygbpmentioning
confidence: 99%
“…Of these substances, only a single dosing regimen of a single substance (exendin-4) was able to produce a sustained ϳ15-30% reduction in daily food intake and weight loss for Ͼ2 wk (31). However, exendin-4's effect waned after 17 days, and coadministration of PYY and exendin-4 at various dosing combinations did not produce a more prolonged effect than the GLP-1 receptor agonist exendin-4 alone despite recent studies suggesting that chronic elevation in gut hormones PYY and GLP-1 may cause the significant weight loss that occurs with Roux-en-Y gastric bypass surgery (19,20).…”
mentioning
confidence: 93%